2016
DOI: 10.1002/joc.4721
|View full text |Cite
|
Sign up to set email alerts
|

Development of moderate-resolution gridded monthly air temperature and degree-day maps for the Labrador-Ungava region of northern Canada

Abstract: Detailed climatological grids are needed for many applications, including permafrost prediction, ecological modelling and infrastructure planning. This study describes the creation of moderate‐resolution gridded climate datasets covering the entire Labrador‐Ungava region (50°–63°N) for a series of climate indices, including monthly air temperature, annual air temperature, freezing degree‐days (FDDs) and thawing degree‐days. Using a recently developed spatiotemporal infilling technique, temporally consistent cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…Labrador has an area of 294 000 km 2 and contains the highest mountains in continental eastern Canada (Torngat Mountains) and the southernmost limits of the Arctic climate region in Canada . Mean annual air temperatures vary from + 1.5 to −9°C and annual temperature amplitudes (AT; July mean minus January mean) vary from 22°C near the coast to 45°C in the interior . Approximately 60% of Labrador is forested (typically black spruce, white spruce, tamarack and birch) while nearly 30% consists of alpine tundra, high sub‐Arctic tundra or low Arctic tundra .…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Labrador has an area of 294 000 km 2 and contains the highest mountains in continental eastern Canada (Torngat Mountains) and the southernmost limits of the Arctic climate region in Canada . Mean annual air temperatures vary from + 1.5 to −9°C and annual temperature amplitudes (AT; July mean minus January mean) vary from 22°C near the coast to 45°C in the interior . Approximately 60% of Labrador is forested (typically black spruce, white spruce, tamarack and birch) while nearly 30% consists of alpine tundra, high sub‐Arctic tundra or low Arctic tundra .…”
Section: Study Areamentioning
confidence: 99%
“…22 Mean annual air temperatures vary from + 1.5 to −9°C and annual temperature amplitudes (AT; July mean minus January mean) vary from 22°C near the coast to 45°C in the interior. 23 Approximately 60% of Labrador is forested (typically black spruce, white spruce, tamarack and birch) while nearly 30% consists of alpine tundra, high sub-Arctic tundra or low Arctic tundra. 24 The remaining area is evenly divided between coastal barrens and wetlands.…”
Section: Study Areamentioning
confidence: 99%
“…The existing research on meteorological factor interpolation adopts different methods-Kriging and IDW (Inverse Distance Weighted) [11,40] for relative humidity, Kriging and IDW [11,32] for precipitation., and TPS (Thin Plate Spline) and Kriging [40,41] for air temperature. Considering that the spatial distribution was significantly different in relative humidity, precipitation, and air temperature, and air temperature had a certain degree of altitude sensitivity [40][41][42], on the basis of the previous study method, after being tested by comparing meteorological site data and other methods, IDW was selected to interpolate the relative humidity, and Kriging to interpolate the precipitation. TPS was selected and DEM acted as the covariate to assist spatial interpolation of air temperature data.…”
Section: Spatial Interpolation Of Meteorological Datamentioning
confidence: 99%
“…They suggest that care should be taken in using these gridded products in local-or regionalscale applications. Additionally, Way et al (2017) recently showed that data taken from a new land-only product developed within the Berkeley Earth Surface Temperatures (BEST) project (Rohde et al 2013), and which were not used by Rapaić et al (2015), reveal an underestimation of recent warming in northern Canada when compared against data taken from the Adjusted and Homogenized Canadian Climate Dataset (ADHCCD) developed by Environment Canada. They also stated that automated station adjustment algorithms reduce air temperature changes in this region and are sensitive to declines in the long-term observing network.…”
Section: Introductionmentioning
confidence: 99%